Biomechanical properties and corrosion resistance of plasma-sprayed fish scale ydroxyapatite (FsHA) and FsHA-doped yttria-stabilized zirconia coatings on Ti-6Al-4V alloy for biomedical applications - Anene, Franklin A.; Jaafar, Che Nor Aiza; Mohamed Ariff, Azmah; Zainol, Ismail; Mohd Tahir, Suraya; Abdul Razak, Bushroa; Salit, Mohd Sapuan; Anene-Amaechi, Joy (Multidisciplinary Digital Publishing Institute, 2023)
Hydroxyapatite (HA) coatings on metallic implants have been extensively used in orthopedic applications to improve tissue-implant interactions, enhance their biocompatibility, and enhance their functionality. However, the expensive synthetic HA is the most widely used bioceramic for implant coatings, leading to high implants costs. Hence, this research explored the potential of an inexpensive biogenic HA derived from fish scales and FsHA/yttria-stabilized zirconia (YSZ) bioceramic coatings on a Ti“6Al“4V alloy as an alternative to synthetic HA coatings. The FsHA/YSZ powders and the coatings were examined with X-ray diffraction (XRD) and scanning electron microscopy/energy dispersive X-ray (SEM/EDX), and the surface roughness, microhardness, corrosion resistance, bioactivity, and in vitro cytotoxicity of the coatings were also determined. The morphological powder analysis revealed particles with a slightly irregular morphology and a fine spherical morphology, while the coating microstructure analysis revealed a fine lamellar morphology, with partially melted and unmelted FsHA particles, and fine microcracks along with evenly dispersed ZrO2 particles. The surface roughness of the FsHA coating increased by 87.5 compared with the uncoated substrate, and the addition of YSZ significantly reduced this value. A 35.5 increase in hardness was obtained in the FsHA + 20 wt. YSZ coating, and the FsHA coating showed a 43.2 reduction in the corrosion rate compared with the uncoated substrate; a further 73 reduction was observed with the addition of YSZ. The microstructure of the coatings after 14 days of immersion in simulated body fluid (SBF) revealed enlarged cracks and delaminated segments with well-grown apatite spherulite layers on the whole surface of the coatings, while in vitro cytotoxicity analysis showed a good cell viability of 95 at the highest concentration of the specimen.